Rice husk filled thermoplastic composite / Ariff Mohamed - Mohamed, Ariff (1999)
A study was conducted on rice husk obtained from Bernas Kuala Selangor, to determine its suitability for thermoplastic manufactured and to determine its physical and mechanical properties. The rice husk and Polypropylene (PP) were blended in a Dispersion Mixer and then moulded into a composite in a mould, with the rice husk weight fractions varying from 10 to 50%. A maleated anhydride polypropylene was used to improve the interaction or poor bonding and adhesion between hydrophobic or non-polar matrix plastic and the polar or hydrophilic lignocellulosic fibers. Form the result; rice husk loading affected the physical and mechanical properties of the composite. Higher amount of rice husk decreased the strength and elongation, while the modulus of elasticity and water absorption properties increased significantly. Present of MAPP increased the strength, modulus of elasticity and elongation but decreased the water absorption significantly. There was little difference in the properties observed between composite with 1% and 3% MAPP (by weight). These results suggest that rice husk is a suitable material to be use in the manufacture of thermoplastic composite.